PEMBERDAYAAN MASYARAKAT NELAYAN DESA LAMU BATUDAA PANTAI MELALUI OLAHAN PRODUK TULANG IKAN TUNA - Nento, Wila Rumina; Olii, Abdul Hafidz; Olii, Salahudin (Jurnal Abdi Insani, 2024)
Lamu Village is a fishing village located on the beach or around the sea waters of Batudaa Beach Regency. Empowering the fishing community in Lamu Village can be important because fishermen are one of the main economic sectors in the village. Apart from that, Lamu Village is a village that is included in the category of villages experiencing extreme levels of poverty. In fact, Lamu Village has a lot of enormous natural potential, one of which is the potential for aquatic products because Lamu Village is in the coastal area of Tomini Bay. However, this enormous potential has not been utilized and managed optimally by the people of Lamu Village. The aim of this community service is to provide information regarding the handling of yellowfin tuna catches and training on diversifying noodle products from fish bones as a source of calcium. The methods used are counseling and training methods or direct demonstrations to the community, especially fishermen and PKK women. The results obtained from this training are that the community is able to process and utilize water products, especially those that are the potential of Lamu Village. The community has been able to make meatballs from tuna meat and noodles from tuna bone meal, which is able to create products that can give birth to MSMEs in the community.